Preparation and characterization of thermo‐responsive shape memory polycaprolactone/poly(ethylene‐co‐octene) blends for 4D printing - Zhu, Lei; Liu, Donglei; Luo, Xin; Zhou, Jingxiang; Zheng, Junjie; Lai, Ciyi (Polymer engineering and science, 2023)
This work focuses on the development of a novel thermo‐responsive shape memory polymer (SMP) for 4D printing by blending polycaprolactone (PCL) and poly(ethylene‐co‐octene) (POE) in various proportions. The SEM images of PCL/POE blends indicate an improvement in phase compatibility with increasing POE content and the formation of a co‐continuous structure. Based on the analysis of DSC curves, the range of transition temperature (Ttrans) was determined to be 55–60°C. Among the tested blends, PCL4/POE6 exhibits the most optimal shape memory performance, in which the shape fixation and recovery rates are above 90% and remain stable even after 10‐cycle testing. It indicates that the formation of co‐continuous phases shows a significant enhancement of shape memory properties. Subsequently, the 3D printing parameters were verified there is no obvious effect on shape memory performance. The network filling method was found to be suitable for printing, and the shape memory performance degraded after the layer thickness exceeded 0.22 mm. To sum up, the results can provide valuable insights and assistance for the development and application of materials with similar shape memory characteristics. This work focus on the development of a novel thermo‐responsive shape memory polymer (SMP) for 4D printing by blending polycaprolactone (PCL) and poly(ethylene‐co‐octene) (POE) in various proportions, and investigating the shape memory property.